Educating Faculty Members on the Importance of Requiring High-Quality Information Resources at a Community College. Issue 1 (2nd April 2016) - Auten, Beth; Glauner, Dana; Lefoe, Grant; Henry, Jo
ABSTRACT: This article explains how the South Piedmont Community College librarians educated faculty members about how they guide student use of the library and how it is advantageous for them to require high-quality resources for student papers. As documented by observations at SPCC and in the library literature, students use the tools they know to find information and are unwilling to change their habits without an outside influence—often the teaching faculty—encouraging the students' use of the library and its resources. Students need good research skills for their college-level academic work, and those skills are also vital as they transfer to other academic programs or enter the workplace. By presenting a professional development session targeted at teaching faculty, librarians influenced a positive shift in faculty requirements for student research.